Lung-heart toxicity in a randomized clinical trial of hypofractionated image guided radiation therapy for breast cancer - Van Parijs, Hilde; Cecilia-Joseph, Elsa; Gorobets, Olena; Storme, Guy; Adriaenssens, Nele; Heyndrickx, Benedicte; Verschraegen, Claire; Nguyen, Nam P.; De Ridder, Mark; Vinh-Hung, Vincent (Frontiers in Oncology, 2023)
Background TomoBreast hypothesized that hypofractionated 15 fractions/3 weeks image-guided radiation therapy (H-IGRT) can reduce lung-heart toxicity, as compared with normofractionated 25-33 fractions/5-7 weeks conventional radiation therapy (CRT). Methods In a single center 123 women with stage I-II operated breast cancer were randomized to receive CRT (N=64) or H-IGRT (N=59). The primary endpoint used a composite four-items measure of the time to 10% alteration in any of patient-reported outcomes, physician clinical evaluation, echocardiography or lung function tests, analyzed by intention-to-treat. Results At 12 years median follow-up, overall and disease-free survivals between randomized arms were comparable, while survival time free from alteration significantly improved with H-IGRT which showed a gain of restricted mean survival time of 1.46 years over CRT, P=0.041. Discussion The finding establishes TomoBreast as a proof-of-concept that hypofractionated image-guided radiation-therapy can improve the sparing of lung-heart function in breast cancer adjuvant therapy without loss in disease-free survival. Hypofractionation is advantageous, conditional on using an advanced radiation technique. Multicenter validation may be warranted. Trial registration: https://clinicaltrials.gov/ct2/show/NCT00459628 . Registered 12 April 2007.